ANALISIS PEMBIAYAAN INVESTASI PADA PEMBANGUNAN PERUMAHAN TAMAN KARANGBAHAGIA TAHAP 1 KABUPATEN BEKASI, JAWA BARAT - Rossy Khairinisa; I Nyoman Dita Pahang Putra; Anna Rumintang (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2020)
In the development planning of a project, a financial analysis is needed that indicates the investment process of the project is feasible. One of the most important aspects of the investment process is the composition of financing. Funding can be divided into two, namely from loans and equity. The study was conducted on the Karangbahagia Park Housing development project in Bekasi, West Java. The purpose of this study was to determine the sensitivity of three different financing compositions. This research was conducted using the Discounted Cash Flow method to calculate the project valuation. Then the investment feasibility is measured by NPV (Net Present Value), IRR (Internal Rate Return), BEP (Break-Even Point) and ROI (Return on Investment) indicators. The three financing compositions to be investigated are 70% loan: 30% equity. 30% loan: 70% equity and 50% loan: 50% equity. The results of the composition sensitivity analysis show that in the composition of 30% loan: 70% equity NPV reached a positive number of IDR.17,485,230,641.00 and IRR 38%. While on the composition of 70% loan: 30% equity NPV negative and IRR reached values of IDR.9,126,201,503.00 and 2%. In the composition of 50% loan: 50% equity, namely NPV reached a value of IDR.4,179,514,569.00 and IRR 21%. BEP occurs after one year and ten months and Return on Investment yields a figure of 16.71% from the composition of 30% loan: 70% loan.